2016
DOI: 10.1021/acs.organomet.6b00240
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Active N-Acylamidine–Zirconium Complexes: Synthesis, Structures, and Application in Ethylene Polymerization

Abstract: Three novel N-acylamidines 1a−c with varying steric bulk and substitution patterns were synthesized and thoroughly characterized by X-ray diffraction. Compounds 1a and 1b, which contain two additional binding sites located at two pyridine substituents, were treated with equimolar amounts of cyclopentadienylzirconium(IV) trichloride at room temperature. The X-ray data of the resulting coordination compounds 7a and 7b indicate the formation of five-membered metallacycles with one of the pyridine nitrogen atoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Interestingly, even the axial interaction with the water molecule (Ni–O2, 2.096 Å) results in a shorter bond than the axial Ni-tertiary amine (N4) bond. The bond lengths of the IDD backbone are between 1.26–1.37 Å for the C–N bonds, falling within the range of precedent M-IDD complexes. , The shortest bond length is the C–O bond (1.262 Å). Close values of C–N and C–O bond lengths are indicative of charge delocalization in a singly deprotonated IDD ligand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, even the axial interaction with the water molecule (Ni–O2, 2.096 Å) results in a shorter bond than the axial Ni-tertiary amine (N4) bond. The bond lengths of the IDD backbone are between 1.26–1.37 Å for the C–N bonds, falling within the range of precedent M-IDD complexes. , The shortest bond length is the C–O bond (1.262 Å). Close values of C–N and C–O bond lengths are indicative of charge delocalization in a singly deprotonated IDD ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Close values of C–N and C–O bond lengths are indicative of charge delocalization in a singly deprotonated IDD ligand. In contrast, protonated IDD ligand free form or metal bound, such as the one found in copper­(II) pyridinophan- N -acetylamidine reported by Mirica et al, showed significant dissymmetry of the backbone, with distinguishable single (C–N, 1.37–1.39 Å) and double (C–O, 1.224 Å; terminal C–N, 1.282 Å) bonds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 20 years N ‐acylamidines have been investigated mainly by the Würthwein group . The three heteroatoms (one oxygen and two nitrogen atoms) offer various coordination modes for transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Würthwein and co‐workers obtained N ‐acylamidine Cu complexes with coordination numbers four, five and six in square planar, tetrahedrally distorted planar, square pyramidal and octahedral coordination, respectively . They further extended the coordination possibilities either by the preparation of Bis( N ‐acylamidines) and Tris( N ‐acylamidines) which allow coordination to more than one metal center or by introduction of substituents (R 1 and R 2 in Figure ) with additional coordination sites like pyridines . However, without these additional binding sites the formation of six‐membered chelate rings, with metal coordination towards the oxygen of the acyl group and the amino nitrogen is most likely.…”
Section: Introductionmentioning
confidence: 99%